ASSESSMENT OF SEMINAL TRAITS AND SUITABILITY OF SEMEN FOR CRYOPRESERVATION OF EXOTIC STALLIONS REARED UNDER INDIAN CONDITIONS - TALLURI, T R; RAVI, S K; LEGHA, R A; YASHPAL; THOMAS, T K; KASHYAP, S S; TRIPATHI, B N (The Indian Journal of Animal Reproduction, 2022)
Semen was collected from seven exotic stallions for the evaluation of seminal characteristics and freezability of semen. The appearance of fresh semen was milky-white to creamy and consistency of gel-free semen was variably thick. The total volume of semen, gel-free semen and gel in semen was 50.28±8.34, 43.57±8.14 and 6.71±3.32 ml, respectively. The mass and progressive sperm motility in gel free semen was 88.71±1.70% and 75.71±1.70%, respectively. Mean sperm concentration in fresh semen was 205.37±12.65 × 106 ml-1. The post-thaw sperm motility was recorded up to an acceptable >30% (40.00±2.43%). The study indicated that the semen from exotic stallions reared in India can be cryopreserved using conventional vapor freezing technique for encouraging artificial insemination and study of their fertility potential.